Assessing The Impact Of Flood Susceptibility Of Real Estate Locations On Real Estate Market Prices Using Geographic Information System (GIS) And Multi Criteria Decision Making (MCDM) Technique - Quan, Seow Zhen (IRC, 2019)
Kelantan is prone to regular flood events due to its geographical characteristics, unplanned urbanization and proximity to South China Sea, and these have catastrophic impacts on the economy, environment and human life. Because of its frequency and intensity, there are concerns that the city’s perennial floods will negatively affect the prices of properties located in the flood plain.